THE MEMORY-GAME–ENHANCED GAME-BASED LEARNING MODEL: HOW EFFECTIVE IS IT IN STRENGTHENING STUDENTS’ LEARNING INTEREST, SPECIFICALLY THEIR ATTENTION? - Adelia Lestarina; M. Indra Saputra; Syaiful Anwar; Baharudin Baharudin (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
This study is driven by the low level of student learning interest in the Islamic Cultural History (Sejarah Kebudayaan Islam/SKI) subject at Pondok Pesantren Darul Huffaz Pesawaran, particularly in the attention indicator, which appears weak under conventional instructional practices. Monotonous learning activities often cause students to become easily bored, lose focus, and engage minimally in classroom tasks. Such conditions underscore the urgency of implementing innovative instructional approaches capable of creating an engaging and interactive learning environment that consistently stimulates students’ attention. Accordingly, this study aims to determine the effectiveness of a Game-Based Learning model using a memory game in enhancing students’ learning interest, particularly in the aspect of attention.The research employed a quantitative approach with a quasi-experimental method and a nonequivalent control group design. Two classes were designated as research samples: an experimental class receiving treatment through the memory game and a control class taught using conventional methods. Data on learning interest were collected through a validated and reliable questionnaire, and subsequently analyzed using normality tests, homogeneity tests, and an independent samples t-test.The findings show that the data were normally distributed and homogeneous. The t-test generated a significance value of 0.031 (< 0.05), indicating a significant difference between the two groups. These results demonstrate that the Game-Based Learning model utilizing a memory game effectively enhances students’ learning interest in terms of attention, reflected in improved focus, active engagement, and concentration during SKI learning activities. In conclusion, the memory game–based Game-Based Learning model constitutes an effective and innovative instructional strategy for fostering students’ learning interest and is suitable for implementation in SKI learning within the pesantren context.